Perceived Social Support and Psychological Well-being of Individuals with Criminal Labels: A Mixed-Methods Sequential Explanatory Study - Mercy Joy De Guzman; Aradela De Castro; Jerwin Mark Cerillo; Andrie Jann Akilith; Glaiza Casaljay; Janela Thea Dela Cruz (Humanities, Society, and Community, 2026)
This study examined the Psychological well-being and social reintegration experiences of individuals with criminal labels in the Philippines, using a mixed-methods sequential explanatory design. The quantitative phase assessed 115 participants under probation supervision using the Psychological Well-being Scale (Ryff, 1989) and the Multidimensional Scale of Perceived Social Support (Zimet et al., 1988). Findings revealed that participants perceived the strongest support from friends (M = 6.13, SD = 1.63) and significant others (M = 6.09, SD = 1.70), while family support was lower (M = 5.30, SD = 2.04). Psychological well-being was highest in Purpose in Life (M = 31.37, SD = 1.92), Self-Acceptance (M = 30.29, SD = 1.91), and Personal Growth (M = 30.17, SD = 1.94), and lowest in Positive Relations with Others (M = 27.42, SD = 2.03), highlighting relational challenges. These results corroborate existing literature on the role of social support in post-incarceration adjustment and the vulnerability of relational domains. The qualitative phase, involving seven participants with extreme PWB scores, identified six themes: Complex Physical Stress, Adaptive Psychological Transitions, Social Reintegration, Ambivalence in Spiritual Coping, Survival Amid Economic Exclusion, and Weight of the Criminal Label. Narratives revealed that participants navigated physical, emotional, spiritual, social, and economic challenges while striving for resilience, acceptance, and self-sufficiency. Interpreted through the Kaginhawaan Theory, the findings underscore the significance of material sufficiency, relational security, and inner peace in culturally grounded well-being. Labeling Theory contextualizes how stigma and societal judgment perpetuate psychological and social barriers, emphasizing the need for interventions that integrate psychosocial support, restorative justice, and community acceptance. The study contributes to Philippine-based reintegration research by combining quantitative and qualitative evidence, highlighting both internal strengths and structural obstacles that influence holistic well-being, social belonging, and sustainable post-incarceration outcomes.